Racemic mefloquinium chlorodifluoroacetate: Crystal structure and Hirshfeld surface analysis - Wardell, James L.; Wardell, Solange M. S. V.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2018)
In the racemic title molecular salt, C17H17F6N2O+.C2ClF2O3 -(systematic name:2-{[2,8-bis(trifluoromethyl)quinolin-4-yl](hydroxy)methyl}piperidin-1-ium chlorodifluoroacetate), the cation, which is protonated at the piperidine N atom, has the shape of the letter, L, with the piperidin-1-ium group being approximately orthogonal to the quinolinyl residue [the Cq—Cm—Cm–Na (q = quinolinyl; m = methine; a = ammonium) torsion angle is 177.79 (18)⁰]. An intramolecular, charge-assisted ammonium-N—H...O(hydroxyl) hydrogen bond ensures the hydroxy-O and ammonium-N atoms lie to the same side of the molecule [Oh—Cm—Cm—Na (h = hydroxyl) = -59.7 (2)⁰]. In the crystal, charge-assisted hydroxyl-O—H...O-(carboxylate) and ammonium-N+—H...O-(carboxylate) hydrogen bonds generate a supramolecular chain along [010]; the chain is consolidated by C—H...O interactions. Links between chains to form supramolecular layers are of the type C—Cl...π(quinolinyl-C6) and the layers thus formed stack along the a-axis direction without directional interactions between them. The analysis of the calculated Hirshfeld surface points to the dominance of F...H contacts to the surface (40.8%) with significant contributions from F...F (10.5%) and C...F (7.0%) contacts.